Sistem Informasi Geografis Tentang Pemetaan Jumlah Rumah Sakit Dan Poliklinik Dikota Semarang - Tarisa Ramadhani; Bambang Agus Herlambang; Khoiriya Latifa (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
Hospitals and polyclinics are professional health care institutions whose services are provided by doctors, nurses and other health experts. As the function of hospitals becomes increasingly vital, every community member is expected to know the locations of the hospitals and polyclinics closest to where they live to anticipate undesirable events. Geographic Information Systems (GIS) is a technology that is currently a very essential tool in storing, manipulating, analyzing and displaying natural conditions with the help of attribute data and spatial data. GIS can represent the real world on a computer monitor just as a map sheet can represent the real world on paper. Under these conditions, this system is very useful in making it easier for the health service to manage and review the location of hospitals in the city of Semarang, so that in the future it can be in line with programs from other agencies involved in managing city spatial planning. The aim of this research is to build a geographic information system with an integrated database, especially to find the locations of hospitals and polyclinics in the city of Semarang. So it can provide information to users who want to find hospital locations in the city of Semarang.